Her secret hope - Gray, Shelley Shepard (Gray, Shelley Shepard. Season in Pinecraft, 2023)
"For Lilly, the Amish town of Pinecraft is a chance to start again. But then she meets Eddie, a man with no plans to stay--a man she can't stop thinking about. She must decide whether to give him up or face her past and hope that their love will endure"--